2018
DOI: 10.3847/1538-4357/aaad10
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase Heating in Flaring Loops

Abstract: We analyze and model a C5.7 two-ribbon solar flare observed by SDO, Hinode and GOES on 2011 December 26. The flare is made of many loops formed and heated successively over one and half hours, and their foot-points are brightened in the UV 1600Å before enhanced soft X-ray and EUV missions are observed in flare loops. Assuming that anchored at each brightened UV pixel is a half flaring loop, we identify more than 6,700 half flaring loops, and infer the heating rate of each loop from the UV light curve at the fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 62 publications
4
39
0
Order By: Relevance
“…Nevertheless, due to the possible non-equilibrium ionization at flare temperatures early in the long tenuous late-phase loop, the bump is absent in the observed AIA 335Å light curve. Recently, Zhu et al (2018) studied a C-class two-ribbon solar flare using the EBTEL model, in which the modeled peaks in AIA 131 and 94Å are also well above the observed peaks (Figure 3 in their paper).…”
Section: Comparison With Observationsmentioning
confidence: 86%
See 2 more Smart Citations
“…Nevertheless, due to the possible non-equilibrium ionization at flare temperatures early in the long tenuous late-phase loop, the bump is absent in the observed AIA 335Å light curve. Recently, Zhu et al (2018) studied a C-class two-ribbon solar flare using the EBTEL model, in which the modeled peaks in AIA 131 and 94Å are also well above the observed peaks (Figure 3 in their paper).…”
Section: Comparison With Observationsmentioning
confidence: 86%
“…During a solar flare, the optically thin C IV lines are significantly enhanced, showing a prompt and sensitive response to the flare energy release. Therefore, the evolution in AIA 1600Å can be regarded as a proxy for flare heating Qiu et al 2012;Zhu et al 2018). The AIA 1600Å intensity profile of the AR (purple) shown in Figure 3(e) reveals two peaks at 12:42:41 and 12:47:53 UT (highlighted by the vertical dashed lines), respectively, indicative of two main episodes of energy release taking place in quick succession.…”
Section: Two-stage Energy Releasementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a recent study by Kuhar et al (2017) has shown that the energy released during the gradual phase is at least an order of magnitude larger than the energy released during the impulsive phase. Models of on-going reconnection have been shown to be compatible with the late-phase properties of flares (Cargill & Priest 1983), and multi-threaded modeling of post-flare loops have been able to reproduce long duration light curves observed with GOES and SDO/AIA (Li et al 2014;Qiu & Longcope 2016;Zhu et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, magnetic reconnection, which occurs in the corona yet can be hardly measured there, is mapped in the lower atmosphere by flare radiation, and the reconnection rate is measured by summing up photospheric magnetic fluxes covered by spreading flare ribbons. This method has been widely used to measure the magnetic reconnection rate (e.g., Qiu et al 2002Qiu et al , 2004Isobe et al 2002;Asai et al 2004;Krucker et al 2005;Miklenic et al 2007;Veronig & Polanec 2015;Kazachenko et al 2017;Zhu et al 2018). In this study, the brightening pixels are collected from AIA imaging observations in 1600Å or 304Å passband to measure the reconnection rate in flares ranging from X-class to B-class.…”
Section: Measurement Of Reconnection Propertiesmentioning
confidence: 99%